Metabolomics advances in chronic atrophic gastritis diagnosis and the integration of traditional Chinese medicine - Yanqun Luo; Haiping Xue; Hongyu Chen; Ying Gao; Guang Ji; Tao Wu (Saudi Pharmaceutical Journal)
Chronic atrophic gastritis (CAG) is a prevalent digestive system disorder characterized by the recurrent damage to the gastric mucosal epithelium, with the potential to progress to gastric cancer. Traditional Chinese medicine (TCM), with its holistic perspective and treatment modalities grounded in syndrome differentiation, provides a distinctive approach to both the prevention and treatment of CAG. This review aims to encapsulate the recent advancements in the application of metabolomics to the diagnosis, pathogenesis, and the TCM-based prevention and treatment of CAG, offering novel insights into the therapeutic and preventive strategies for the disease. A systematic analysis was performed on the literature from 2013 to 2024, focusing on studies that utilized metabolomics to investigate the effects of TCM on CAG. The data was sourced from reputable electronic databases including PubMed and Web of Science. The review emphasizes the utility of metabolomics in identifying biomarkers and metabolic pathways associated with CAG and illustrates the capacity of TCM to influence and ameliorate CAG conditions through various mechanisms, including the regulation of gut microbiota and modulation of specific metabolic pathways. This review presents that metabolomics can offer new perspectives for the application of TCM in CAG management, demonstrating significant potential in elucidating the pathogenesis of CAG and in identifying potential therapeutic targets. The convergence of TCM with metabolomics heralds a promising avenue for the personalized treatment of CAG.